1993
DOI: 10.1007/bf02373085
|View full text |Cite
|
Sign up to set email alerts
|

Microcharops anticarsiae (Hym.: Ichneumonidae) parasitoid ofAnticarsia gemmatalis (Lep.: Noctuidae): Host age preference, sex ratio effects and functional response

Abstract: The endoparasite, Microcharops anticarsiae Gupta, is one of the natural control agents of Anticarsia gemmatalis H/.ibner. The effects of host age on the levels of parasitisation and the sex ratio of the subsequent progeny, together with the functional response of M. anticarsiae at 6 different host densities, were evaluated experimentally. In choice experiments involving two or four consecutive instars, female parasitoids showed no preference for host larvae of a particular age. The sex ratio of the parasitoids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…These data showed that there were no cues which allowed the female wasps to discriminate hosts of different ages from a distance. Other parasitoid species, i.e., Microcharophis anticarsiae, a larval parasitoid of Anticarsia gemmatalis (Patel and Habib, 1993) and Microplitis croceipes, a larval parasitoid of soybean and corn pests (Harrison et al, 1993) also showed no preference for hosts of particular age and no host-age effect on host suitability.…”
Section: Discussionmentioning
confidence: 99%
“…These data showed that there were no cues which allowed the female wasps to discriminate hosts of different ages from a distance. Other parasitoid species, i.e., Microcharophis anticarsiae, a larval parasitoid of Anticarsia gemmatalis (Patel and Habib, 1993) and Microplitis croceipes, a larval parasitoid of soybean and corn pests (Harrison et al, 1993) also showed no preference for hosts of particular age and no host-age effect on host suitability.…”
Section: Discussionmentioning
confidence: 99%
“…Among entomophagous wasps, species belonging to two genera, Glyptapanteles (Braconidae) and Microcharops (Ichneumonidae) are usually found acting all over the soybean season (PATEL, 1991). Of all the parasitoid species, attacking A. gernmatalis, Microcharops anticarsiae Gupta is the most frequent in all soybeanproducing states (CORREA, 1979;PATEL, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Among entomophagous wasps, species belonging to two genera, Glyptapanteles (Braconidae) and Microcharops (Ichneumonidae) are usually found acting all over the soybean season (PATEL, 1991). Of all the parasitoid species, attacking A. gernmatalis, Microcharops anticarsiae Gupta is the most frequent in all soybeanproducing states (CORREA, 1979;PATEL, 1991). It is a naturally dominant and efficient controlling agent of A. gemmatalis and also parasitizes other soybean lepidopterous pests: Pseudoplusia includens, Hedylepta indicata (PATEL, 1991) and Spodoptera latifacia (CORREA, 1979).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations